Shariah Governance Structure of Islamic Financial Institutions in Sri Lanka - Hassan, Rusni; Ahamed Hilmy, Hayathu Mohamed (New Millennium Discoveries, UK, 2019)
Shariah governance plays a key role in ensuring integrity of Islamic financial system. The structure and the process of Shariah governance has been proposed by the international standard setting bodies for Islamic Financial Institutions (IFIs) to follow and incorporate Shariah governance practices in their operations and financial products. This study aims to investigate the Shariah governance practice in Sri Lanka that practices dual financial system (conventional and Islamic finance) for the past twenty years, with a special focus on process and structure. The qualitative method is employed in this study whereby the primary data are gathered in the form of interview while secondary data are collected through research articles, annual reports, official websites, magazines and newspaper. This study found there are gaps and shortcomings in the Shariah governance practice at IFIs in Sri Lanka particularly in the structure and the process as compare to the international framework and guidelines issued by international standard setting body such as AAOIFI and IFSB. The main contribution of this study is to put forward recommendations to rectify the gaps and to further enhance the Shariah governance practices in Sri Lankan IFIs.